Kepemimpinan Kaum Minoritas: Analisis Teks Keluaran 1-2 - Panca Parulian S. (EDULEAD: Journal of Christian Education and Leadership, 2021)
Leadership always looks at three main aspects: the leader, the follower, and the situation. These three aspects also make leadership theory always tested in new contexts so that experts continue to seek which leadership theory is most effective in specific contexts. This has the consequence of the dominance of research related to leadership in the organizational context, which is also seen in Christian leadership studies in constructing Christian leadership. Analysis of Christian leadership usually focuses on God and one particular character. This article explains that at least three main aspects are needed to examine Christian leadership: theological, leadership process, and reflective. This article offers to read the text in its entirety and pay attention to each of the roles involved. Reading the text of Exodus 1-2 finds the leadership of the minority against the rulers, namely the midwives and Moses: creative disobedience and the death of a vision. Thorough leadership analysis is needed in building Christian leadership. Abstrak Kepemimpinan selalu melihat tiga aspek utama: pemimpin, pengikut, dan situasi. Tiga aspek itu juga yang membuat teori kepemimpinan selalu diuji dalam konteks yang selalu baru, sehingga para ahli terus mengupayakan teori kepemimpinan mana yang paling efektif dalam konteks tertentu. Hal itu memberikan konsekuensi dominasi penelitian terkait kepemimpinan dalam konteks organisasi terlihat juga dalam penelitian-penelitian kepemimpinan Kristen dalam mengonstruksi kepemimpinan Kristen. Analisis kepemimpinan Kristen biasanya terfokus pada Allah dan satu tokoh tertentu saja. Artikel ini memberikan pemahaman setidaknya diperlukan tiga aspek utama untuk mengkaji kepemimpinan Kristen: teologis, proses kepemimpinan, dan reflektif. Artikel ini menawarkan untuk membaca teks secara menyeluruh dan memerhatikan setiap peran yang terlibat. Pembacaan teks Keluaran 1-2 menemukan kepemimpinan dari kaum minoritas terhadap penguasa, yakni para bidan-bidan dan Musa: creative disobedience dan the death of vision. Analisis kepemimpinan yang menyeluruh diperlukan dalam membangun kepemimpinan Kristen.